Clinical Profile of Childhood Optic Neuritis in a Tertiary Care Hospital of Bangladesh - Khan, Husnea Ara; Islam, Ariful; Saha, Dipa; Nayeem, Abu; Parvin, Jobaida; Rahman, AKM Sharifur (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Childhood optic neuritis is rare and distinct from that which occurs in adults. Visual prognosis is better in children despite severe vision loss at the initial phase. Proper understanding the clinical profile of optic neuritis in children may make an opening to find out a better management plan. Materials and Methods: This cross-sectional study was conducted at the Department of Pediatric Neurology, National Institute of Neurosciences and Hospital. Total 24 children of 5- 15 years old with acute or subacute loss of vision were enrolled from January 2020 to December 2020. Then thorough evaluation was done by taking history, physical, neurological, and ophthalmological examinations. Cerebrospinal fluid (CSF) study, neuroimaging of orbit, brain, and spine, and anti- NMO Ab were done subsequently. Result: Mean age was 9.57±2.70 years with female (66.67%) predominance. Bilateral ocular involvement 19(79.17%) and ocular pain 18(75%) were the main presenting feature and isolated optic neuritis (79%) were the most common cause followed by 13% of optic neuritis- neuromyelitis optica (ON-NMO), 4% of optic neuritis-clinically isolated syndrome (ON-CIS) and Optic neuritis- acute disseminated encephalomyelitis (4%). Optic nerve hyperintensity 8(33.33%) were common orbital MRI findings in isolated optic neuritis where 2(8.3%) ADEM had abnormal brain MRI and 3(12.5%) ON-NMO had abnormal MRI of spine Conclusion: Most childhood optic neuritis cases were isolated in nature with bilateral involvement. Optic disc oedema was frequent. J Bangladesh Coll Phys Surg 2025; 43: 127-133